2019
DOI: 10.1038/s41598-019-48461-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel bispecific antibody platform to direct complement activity for efficient lysis of target cells

Abstract: Harnessing complement-mediated cytotoxicity by therapeutic antibodies has been limited because of dependency on size and density of antigen, structural constraints resulting from orientation of antibody binding, and blockade of complement activation by inhibitors expressed on target cells. We developed a modular bispecific antibody platform that directs the complement-initiating protein C1q to target cells, increases local complement deposition and induces cytotoxicity against target antigens with a wide-range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…C1qNb75 does not bind to mouse C1q (data not shown). This prevents application of the C1qNb75 in murine animal models of complement associated pathogenesis unless mouse C1q is fully or partially replaced by human C1q as described in ( 47 ). Sequence alignment of the gC1q epitope from common model animals ( Figure S2A ) suggests that C1qNb75 can be useful in non-murine animal models including primate models of delayed graft function ( 48 ) and a pig model of ischemia-reperfusion injury ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…C1qNb75 does not bind to mouse C1q (data not shown). This prevents application of the C1qNb75 in murine animal models of complement associated pathogenesis unless mouse C1q is fully or partially replaced by human C1q as described in ( 47 ). Sequence alignment of the gC1q epitope from common model animals ( Figure S2A ) suggests that C1qNb75 can be useful in non-murine animal models including primate models of delayed graft function ( 48 ) and a pig model of ischemia-reperfusion injury ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complement regulatory factor‐neutralizing and tumor‐targeting antibodies have been delivered in mAb cocktails, 14 as well as combined in bispecific mAbs 15 . A novel bispecific, targeting both CD20 antigen and the C1q globular head, was recently reported that provides a direct means of C1q recruitment that may additionally provide enhanced flexibility and relieve geometric constraints tied to antigen and epitope specificity 16 . Direct modification of the antibody molecule in bispecific strategies such as this, or more commonly by Fc engineering (Table 1) not only contributes to drug optimization, but has also served as a key tool for determining antibody mechanism of action.…”
Section: Antibody Engineeringmentioning
confidence: 99%
“…Animal models have been extensively used to parse the mechanisms of action of pathogenic or protective antibodies with a diversity of genetic knockouts, 121,122 human cascade component knock‐ins 16 and complement‐modifying interventions including C5 and/or C3 depletion using cobra venom factors 123 . While animal models have demonstrated an indispensable role here, species‐specific and human allelic differences in each of the many complement factors can also influence outcomes.…”
Section: Modeling the Contribution Of Complementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, C1qNb75 may still be useful in transgenic murine disease models where the human genes for the three C1q subunit fully or partially replaces the murine C1q genes. Such a chimeric C1q was recently used to evaluate the in vivo potential of a bispecific antibody allowing the targeting of human C1q to infectious microorganisms and cancer cells [ 103 ].…”
Section: The Complement-targeting Nanobodiesmentioning
confidence: 99%